2021
DOI: 10.1111/jfr3.12763
|View full text |Cite
|
Sign up to set email alerts
|

Coupling a land surface model with a hydrodynamic model for regional flood risk assessment due to climate change: Application to the Susquehanna River near Harrisburg, Pennsylvania

Abstract: An increase in heavy precipitation associated with climate change has exacerbated flooding in the Eastern U.S. To assess regional flood risk with changing climatic conditions, we demonstrate the application of a novel hydrologic modeling framework that integrates climate projections with a coupled Noah‐MP land surface model and a two‐dimensional HEC‐RAS hydrodynamic model. We employ this framework along a 41 km reach of the Susquehanna River near Harrisburg, Pennsylvania, where recent flood damages exceeded $2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Because of this, modelers should consider a range of ratios of channel width to resolution that would work for their study sites. To contextualize our findings with other hydrodynamic modeling studies, we found that channel width to DEM resolution ratio tends to range from 2 to 175 (Abu-Aly et al, 2014;Cobby et al, 2003;Cook & Merwade, 2009;Mason et al, 2003;Modi et al, 2022;Papaioannou et al, 2020). Mesh grid resolution was not clearly reported in the cited literature, thus we cannot comment on that ratio.…”
Section: Discussionsupporting
confidence: 77%
“…Because of this, modelers should consider a range of ratios of channel width to resolution that would work for their study sites. To contextualize our findings with other hydrodynamic modeling studies, we found that channel width to DEM resolution ratio tends to range from 2 to 175 (Abu-Aly et al, 2014;Cobby et al, 2003;Cook & Merwade, 2009;Mason et al, 2003;Modi et al, 2022;Papaioannou et al, 2020). Mesh grid resolution was not clearly reported in the cited literature, thus we cannot comment on that ratio.…”
Section: Discussionsupporting
confidence: 77%
“…Flood disasters are a major concern in many regions of the world due to the recent increase in the frequency of short-duration floods caused by climate change [1][2][3]. In particular, short-duration rainfall extremes cause the collapse of irrigation structures and residential facilities, the burial of agricultural land, and the deterioration of river water quality, resulting in socioeconomic losses [4,5].…”
Section: Introductionmentioning
confidence: 99%